Time for education on sustainable development - Abd Razak, Dzulkifli (2005)
NEVER before has the need for sustainable development been more apparent and urgent than the last couple of months when the issue of petroleum price hike and the lingering AP controversy became the talk of the town. The need for sustainable development was especially felt when vehicles turned up at the petrol stations at the end of last month, no thanks to a further surge in crude oil price — now exceeding US$65 per barrel. The Government had no choice but to review subsidies for petrol and diesel, said to be the cheapest in the region. Otherwise, activities such as smuggling and the inefficient use and wasteful of the nonrenewable energy source would continue to be unchecked. More so, as the demand for oil is expected to be on an upward trend (sometimes artificially induced), highlighting the longfelt concern as to how much longer can Malaysia supports its future energy needs.